First record of Alectorobius coniceps (Ixodoidea: Argasidae) and Dermacentor sp. (Ixodoidea: Ixodidae) in Pakistan - Ali, Abid; Khan, Mehran; Ullah, Zafar; Numan, Muhammad; Tsai, Kun-Hsien; Alouffi, Abdulaziz; Almutairi, Mashal M.; Tanaka, Tetsuya (Frontiers in Veterinary Science, 2024)
Alectorobius species are soft ticks primarily infesting birds, including swallows, while Dermacentor species are hard ticks mainly infesting mammals, including small ruminants. This study for the first time reported two tick species including A. coniceps and a Dermacentor sp. on both morphological and molecular bases in Pakistan. The former species was examined in small ruminants in Balochistan province, while the latter species was examined in swallows' nests in Khyber Pakhtunkhwa province. In total, 25 ticks were collected, with 14 ticks morphologically identified as A. coniceps (males = 9 and females = 5) and 11 ticks identified as Dermacentor sp. (males = 7 and females = 4). Following morphological identification, molecular identification was gained by obtaining 16S rDNA and cox1 sequences for these ticks. The BLAST results for the 16S rDNA and cox1 sequences from A. coniceps shared maximum identity of 97.46% and 96.49% with the same species from Malta. The BLAST analysis of the 16S rDNA and cox1 sequences from Dermacentor sp. showed maximum identities of 98.42% and 97.45% with Dermacentor pavlovskyi from China. The phylogenetic analysis based on 16S rDNA and cox1 of A. coniceps showed a close evolutionary relationship with the same species. In the case of Dermacentor sp., based on 16S DNA and cox1, indicated a close evolutionary relationship with Dermacentor pavlovskyi from China.